Digital Transformation in Public Sector Institutions: A Systematic Literature Review and Comparative Country Analysis - Riyanto Wujarso; Arief Rahman Hakim; Nurul Faizah; Verdi Yasin; Revan Andhitiyara (AL-ISHLAH: Jurnal Pendidikan, 2025)
Digital transformation has become a strategic priority for governments seeking to enhance efficiency, service quality, and citizen engagement. Despite growing interest, empirical and conceptual insights remain fragmented. This study aims to systematically synthesize existing research on digital transformation in the public sector and to identify key benefits, challenges, and implementation approaches. Following PRISMA guidelines, a systematic literature review was conducted using reputable academic databases and official government sources. A total of 28 empirical and conceptual studies met the predefined inclusion criteria. The selected studies were analyzed using thematic analysis to extract recurring patterns, governance contexts, and strategic implications. The findings indicate that digital transformation in government yields significant benefits, including improved cost efficiency, enhanced public service delivery, and greater citizen participation. Cross-country evidence from cases such as Singapore, Australia, and South Korea demonstrates that governance structures, institutional capacity, and policy alignment critically influence the design and outcomes of digital initiatives. However, persistent challenges remain, notably data security and privacy risks, limited resources, and resistance to organizational change. Based on the synthesized evidence, this study proposes a Citizen-Centric Adaptive Model that emphasizes iterative development, data-driven decision-making, and participatory engagement. The study concludes that digital transformation represents a strategic opportunity for governments to improve effectiveness and public satisfaction, while offering practical guidance for policymakers seeking to modernize public sector operations.